Surface passivation of industrial crystalline silicon solar cells - John, Joachim, 1966- (IET energy engineering series, 2018)
This timely, comprehensive work on solar cell surface passivation will collect and convey the scientific and technological progress provided by universities, research institutes and companies to implement dielectric passivation layers into the solar cell manufacturing process for c-Si solar cells.